2019
DOI: 10.1002/prca.201900028
|View full text |Cite
|
Sign up to set email alerts
|

In‐Depth Proteomic Analysis of Human Bronchoalveolar Lavage Fluid toward the Biomarker Discovery for Lung Cancers

Abstract: Purpose Lung cancer is among the most common cancers. Bronchoalveolar lavage fluid (BALF) can be easily obtained from patients with lung cancers. The aim is to develop a novel proteomic method of the molecule‐based sensitive detection of biomarkers from BALF. Experimental Design BALF samples are collected from segmental bronchus of 14 patients with lung cancers from Kyung Hee University Hospital. First, BALF proteome is depleted using a depletion column, and then peptides are prepared from the enriched low ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 22 publications
2
32
0
Order By: Relevance
“…All focused attention on lacritin's two C-terminal amphipathic α-helices required for ligation of heparanase-modified cell surface syndecan-1 ( 53 , 63 ) necessary for epithelial targeting. Their similarity to N- and C-termini of processed lipid stabilizing pulmonary surfactant protein B ( 32 , 33 , 34 ), together with lacritin's detection in broncheoalveolar lavage ( 19 , 20 ), and selective lacritin and C-terminal proteoform deficiency in dry eye were rationale for testing with tear lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All focused attention on lacritin's two C-terminal amphipathic α-helices required for ligation of heparanase-modified cell surface syndecan-1 ( 53 , 63 ) necessary for epithelial targeting. Their similarity to N- and C-termini of processed lipid stabilizing pulmonary surfactant protein B ( 32 , 33 , 34 ), together with lacritin's detection in broncheoalveolar lavage ( 19 , 20 ), and selective lacritin and C-terminal proteoform deficiency in dry eye were rationale for testing with tear lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in dry eye, surprisingly few tear proteins are selectively deficient. Of tear deficient proteins curiously also constituents of broncheoalveolar lung lavage ( 19 , 20 ) are: zymogen granule protein 16B, annexin A5, alpha-2-glycoprotein 1, deleted in malignant brain tumors1, lipocalin-1, submaxillary gland androgen regulator protein 3B, immunoglobulin heavy constant alpha 1, polymeric immmunoglobulin and lacritin. Lacritin is a basal tearing agonist ( 21 , 22 , 23 , 24 ) that in addition transiently stimulates autophagy in ocular surface epithelia ( 25 ) to restore oxidative phosphorylation under conditions of inflammatory stress ( 25 ).…”
mentioning
confidence: 99%
“…Deep protein coverage is paramount for identifying cancer signatures as well as contributing to the design of novel therapies [ 4 ]. Recent methodologies combining antibody-based depletion of high abundant BALF proteins, high pH peptide fractionation, and label-free quantitation on a high-resolution Orbitrap Fusion Lumos instrument demonstrated superior protein coverage [ 16 ]. In this study, we demonstrated the enrichment of sEVs by the sequential centrifugation method and quantification, resulted in a total of 7484 protein isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant proteins like albumin partially hamper the protein coverage obtainable by direct LC-MS analysis of acellular BAL samples. Therefore, Sim et al [ 16 ] established a novel methodology based on combining antibody-based depletion of high abundant BALF proteins, high pH peptide fractionation, and label-free quantitation on a high-resolution Orbitrap Fusion Lumos instrument. However, antibody depletion of abundant proteins risks the removal of clinically relevant target proteins.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach suffers from a major limitation: the abundance of host proteins hampers the detection of pathogen-derived proteins that are usually present at lower concentrations. Recent advances in gel-free sample preparation methods and instrumentation developments for bottomup proteomics using liquid chromatography tandem mass spectrometry (LC-MS/MS) allow exhaustive analysis of even low abundant proteins in complex biological samples due to improvements in speed, mass resolution, sensitivity, as well as ion separation and dissociation technologies [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%